SAT0003 PIM1 REGULATES CD4+ T CELL EFFECTOR FUNCTION IN EARLY RHEUMATOID ARTHRITIS AND HAS POTENTIAL FOR USE AS A NOVEL, MEASURABLE THERAPEUTIC TARGET. (June 2019) - Maney, Nicola J.; Anderson, Amy; Isaacs, John; Pratt, Arthur
Abstract : Background: We previously showed PIM1, among other STAT3-target genes, to be strikingly upregulated in circulating CD4+ T cells of treatment-naïve 'early' rheumatoid arthritis (eRA) patients 1, 2 . PIM1 has a recognised role in T cell development, has been implicated in the pathogenesis of autoimmunity 3, and is the target of specific inhibitors in clinical development in oncology; for example PIM1 was recently identified as a promising target in triple-negative breast tumours 4 . Objectives: We sought to understand the relevance of dysregulated PIM1 gene transcription for T-cell pathobiology during disease initiation and to determine the effects of its inhibition on T cell function. We hypothesised that, amongst a readily-identifiable, high PIM1 expressing subgroup of eRA patients, PIM1 overexpression in CD4+ T cells is a targetable early event in pathogenesis that lies downstream of STAT3-mediated IL-6 signalling. Methods: Peripheral blood was obtained from consenting treatment-naïve arthritis patients or healthy donors and highly pure CD4+ T cells were isolated. PIM1 knock-down (SMARTpool siRNA, Dharmacon) or protein inhibition (small molecule inhibitors; PIM1-selective TCS-PIM-1 1, Tocris and panPIM AZD1208) was undertaken. Flow cytometric analysis was then used to assess activation and proliferation following CD3/CD28-mediated stimulation. Results: In eRA, ex vivo CD4+ T cells exhibited an activated, hyper-proliferative phenotype compared with those isolated from healthy donors. Significantly higher PIM1 mRNA expression in CD4+ T cells was seen using PrimeFlow (flow cytometry) compared to that of other inflammatory arthritidies. Both PIM1 knock-down, PIM1-specific and panPIM inhibition decreased the activation and proliferation of stimulated eRA (Figure 1A ) and healthy donor CD4+ T cells. Moreover, in eRA, PIM1 and panPIM inhibition increased FoxP3 expression (Figure 1B ) and increased the proportion of regulatory T cells (Figure 1C ). Conclusion: Taken together, these data implicate PIM1 as prominent among genes whose induction may "pre-programme" CD4+ T cells to function aberrantly in disease. Conceivably, targeting PIM1 may prove an attractive approach to regulating aberrant CD4+ T cell effector function in an identifiable sub-population of early RA patients that exhibit high CD4+ T cell PIM1 expression in their peripheral blood. References: [1] Pratt AGet al, Ann Rheum Dis2012; 71(8) 1374-81 [2] Anderson AEet al, Rheumatology2018 (in press) [3] Li Z, et al. J Biol Chem2014; 289(39):26872-81 [4] Horiuchi D, et al. Nature Medicine22(11):1321-9 Disclosure of Interests: Nicola J Maney: None declared, Amy Anderson: None declared, John Isaacs Grant/research support from: Pfizer, Grant/research support from: Pfizer, Consultant for: Abbvie, Pfizer, Roche, Galvani, Merck, Gilead, Eli Lilly, Amgen, Janssen, Celltrion, NAPP, Consultant for: Abbvie, Pfizer, Roche, Galvani, Merck, Gilead, Eli Lilly, Amgen, Janssen, Celltrion, NAPP, Speakers bureau: Abbvie, Pfizer, Eli Lilly, Speakers bureau: Abbvie, Pfizer, Eli Lilly, Arthur Pratt Grant/research support from: Dr. Pratt is in receipt of an externally peer-reviewed Investigator Initiated Research grant from Pfizer (£66, 000)., Grant/research support from: Dr. Pratt is in receipt of an externally peer-reviewed Investigator Initiated Research grant from Pfizer (£66, 000)., Speakers bureau: Dr Pratt has received honoraria from Eli Lilly and Janssen-Cilag Ltd. for his time in preparing presentations for non-promotional meetings that have been paid directly to Newcastle University., Speakers bureau: Dr Pratt has received honoraria from Eli Lilly and Janssen-Cilag Ltd. for his time in preparing presentations for non-promotional meetings that have been paid directly to Newcastle University.